Impact of External Environmental Changes and Job Characteristics on Corporate Transformation: A Qualitative Analysis of the Case of Female CEO - Yoshiko SUGIYAMA (AAOS Transactions)
What mechanisms are behind the cases of women being promoted within companies to become representative directors and recover corporate performance in Japanese listed companies? In this exploratory qualitative study based on two interviews with women as president of a traditional Japanese manufacturing company, we identified the factors. The results suggest that the presence of statistical discrimination against women in a long-standing, underperforming company is associated with independence from the core of the organization, with departments and managers with old-fashioned business practices. In Japan, the absence of women in the central network of a company is considered to be a challenge for the promotion of women to management positions, but in this study, rather, having a network of research departments outside the company in new fields and obtaining research funding from outside even without a budget, led to the breakaway from ailing central business units, especially to the appointment of a representative director and president. This was an achievement that led to her appointment as representative director. After becoming president, she had an impact on the company’s reforms and performance improvement, transforming the board of directors into a substantive discussion forum and reorganizing subsidiaries.